SIMULATION OF ON GRID SOLAR POWER PLANT POTENTIAL AT PT. HALMAHERA JAYA FERONIKEL EMPLOYEES HOUSING - Asmawaty Azis; Kurniawan Harun Rasyid; Ilham Adam (Jurusan Pendidikan Teknik Elektro, 2024)
Simulation of On Grid Solar Power Plant Potential at PT. Halmahera Jaya Feronikel Employee Housing , Ilham Adam. In today's era of globalization, the need for electrical energy sources is a major factor in life. Various routine activities carried out by humans every day are not far from electronic goods, making electricity a basic need. The need for electricity also plays a very important role in industry and mining such as at the PT. Halmahera Jaya Feronikel mess which consumes quite high electrical energy, which is around 255 kWh/day, besides that in the PT. Halmahera Jaya Feronikel employee mess area has a mess roof that can be used to make solar power generators and the location of the employee mess is quite strategic because it is free from tall buildings that can cause shadows or shading. The results of the on-grid solar power plant simulation using 98 solar panels with a capacity of 550 Wp and 7 inverters with a capacity of 10 kW, the effective energy that can be generated in this solar power plant based on PVsyst software is 82303 kWh/year with an initial investment value of Rp. 792,040,000 and operational and maintenance costs for 20 years which is the project life of Rp. 438,408,000, with a payback period of 7.9 years and a net present value of Rp. 1,205,963,279 and can be said to be feasible because the NPV value is more than 0 which means that this solar power plant does not experience losses, and the Benefit cost ratio value obtained is 2.57 and can be said to be feasible because the results of the BCR are more than 1 which are obtained from the results obtained with the costs incurred.